2005
DOI: 10.1016/j.intcom.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of building social intelligence in a robotic interface for the home

Abstract: This paper reports an exploration of the concept of social intelligence in the context of designing home dialogue systems for an Ambient Intelligence home. It describes a Wizard of Oz experiment involving a robotic interface capable of simulating several human social behaviours. Our results show that endowing a home dialogue system with some social intelligence will: (a) create a positive bias in the user's perception of technology in the home environment, (b) enhance user acceptance for the home dialogue syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 15 publications
8
97
1
1
Order By: Relevance
“…Trust The concept of Trust not only emerged from our own findings [29], it is also found in studies concerning robot technology [31,49,50] and human-robot interaction [25,30,51]. To incorporate Trust into the model, two items were developed to measure the trust the user has in the robot and to what extent the user intends to comply to the robot's advice and on the nature of human-robot interaction.…”
Section: Additional Constructsmentioning
confidence: 90%
See 1 more Smart Citation
“…Trust The concept of Trust not only emerged from our own findings [29], it is also found in studies concerning robot technology [31,49,50] and human-robot interaction [25,30,51]. To incorporate Trust into the model, two items were developed to measure the trust the user has in the robot and to what extent the user intends to comply to the robot's advice and on the nature of human-robot interaction.…”
Section: Additional Constructsmentioning
confidence: 90%
“…Gender, Age, Experience and Voluntariness of use were found to be the main moderating influences. The model has been applied by De Ruyter et al [30] to investigate the acceptance of a social robot (the iCat). These studies found that participants judged an extravert robot (more expressive in voice and facial expressions) to be more socially intelligent and they were more likely to accept the expressive robot compared with the robot in an introvert condition.…”
Section: Utaut and The Acceptance Of Social Agentsmentioning
confidence: 99%
“…In this study, our objective was to evaluate the participant perception, attitude and intention of use a SAR platform in their profession. To this end we adopted the UTAUT model as proposed by Heerink et al [54], which has been widely used for the evaluation of SAR platforms and has been found to be highly reliable in several previous studies (among others: [25,[55][56][57][58]). …”
Section: Technology Acceptance Models and Hypothesesmentioning
confidence: 99%
“…This requires very rich, privacy-sensitive models of users that go beyond simple habits and preferences, and include aspects of their personality, their health status, the social network and context, etc. It requires embedding ambient intelligence in the social context of a person, a notion that extends the definition of ambient intelligence to cover also aspects of social intelligence [18].…”
Section: Customization and Tailoring Adjusts Messages And Content To mentioning
confidence: 99%